Design of a Web-Based E-Correspondence System for the Secretariat Division of BPBD Binjai City - Dwi Azzahra Siregar; Rio Septian Hardinata; Barany Fachri (Bahasa Indonesia, 2026)
The development of information technology has encouraged various government agencies to implement digital transformation in their administrative processes, including letter management. The Secretariat Department of the Regional Disaster Management Agency (BPBD) of Binjai City currently manages incoming and outgoing letters manually using agenda books and physical document storage. This condition has led to several problems, such as difficulties in retrieving archives, the risk of document loss, and delays in letter distribution. This study aims to design a Web-Based E-Correspondence System that can support the processes of recording, storing, searching, and managing letters within the Secretariat Department of BPBD Binjai City. To develop the proposed system, this research adopts the Design Thinking approach, which consists of five stages: empathize, define, ideate, prototype, and test. The system is designed using the Laravel Framework based on PHP with a MySQL database. The result of this research is a Web-Based E-Correspondence System design that supports letters administration processes to become more effective, structured, and user-friendly for employees.